Use of electronic resources by the undergraduate students of Mapua Institute of Technology, Makati Campus - Tavora, Hazel Anne B.; Cabbab, Johann Frederick A.; Lapuz, Elvira B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2012)
The purpose of this study is to determine use of electronic resources by the undergraduate students of Mapua Institute of Technology, Makati Campus mainly to (1) Find out the frequency of use of the electronic resources by the undergraduate students (2) Determine the factors that the undergraduate students consider in searching information from electronic resources and to (3) Identify how the undergraduate students seek information from the electronic resources.
Three hundred thirty seven survey questionnaires were distributed to undergraduate students enrolled in various programs such as Computer Science (CS), Information Technology (IT), Information Systems (IS), Business Administration (BA), Hotel and Restaurant Management (HRM), Entrepreneurship (ENT), Accountancy (ACT), Nursing (NRS). Purposive convenience sampling was used as the preferred sampling method due to the large sample size.
From the results of this study, it is concluded that 51.2 of undergraduate students of Mapua Makati are not aware of the existence of the library information literacy program / library orientation while 40.5 respondents were able to attend the library orientation.
Special Problem (Master of Library and Information Science)
Keywords: Mapua Institute of Technology. -- Makati Campus -- Students; Electronic information resources -- Use studies; Electronic information resources -- Philippines